Gestión pedagógica en el aula: Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica de los centros educativos Eloy Alfaro y Daniel Martínez de la ciudad de Zamora cantón, Zamora provincia de Zamora Chinchipe, en el año lectivo 2011 – 2012. - Rivera Torres, Carmen Sulema (2013)
The research topic: Educational Management in the Classroom: "school social climate, from the perception of students and teachers of the seventh year of basic education schools Eloy Alfaro and Daniel Martinez, the city of Zamora Canton: Zamora, Province Zamora Chinchipe, 2011-2012 "is irrelevant local, national and global levels. Aims to better understand learning management and classroom social climate, measuring elements and description of the environment in which it develops the students' educational process of the seventh year of basic education. Constituted research shows 2 teachers and 37 children, who were applied questionnaires school social climate, self-assessment and evaluation. Once the investigation is concluded that urban institution meets good learning management and positive school social climate. In rural institution these dimensions reach a regular assessment. What determines conclusions and recommendations with a proposal for teacher professional development. To strengthen educational management of rural school "Daniel Martinez" Canton Zamora, Zamora Chinchipe school year 2013 - 2014 ".